"Shopping for Items" or "Partnering for Performance"? A framework of purchasing practices for value co-creation in post-outsourcing buyer–supplier relationships. Issue 7 (6th August 2018) - Makkonen, Hannu; Nordberg-Davies, Sini; Olkkonen, Rami
Abstract : Purpose: The article aims to further understanding of purchasing practices in post-outsourcing buyer–supplier relationships, and it provides a holistic approach and onceptualizations with which to balance the perspectives of purchasing as an intra-firm operational function and as a strategic activity embedded in relationship and network management. Design/methodology/approach: The research is based on an inductive-oriented case study. The data comprised 61 thematic interviews conducted at 17 buyer companies (electricity distribution companies), 11 service supplier companies and six third-party organizations. The case features a setting in which a growing number of electricity distribution companies have outsourced operational functions regarding network construction, maintenance and fault repair and purchased these services from service suppliers representing a developing service market. Findings: The study explicates the role of purchasing as an element with the most impact on post-outsourcing buyer–supplier relationship outcomes and development. The performance of the buyer–supplier relationship either accelerates or inhibits the new service supplier's entry to the field and motivates or demotivates the electricity distribution companies to outsource their activities. This mechanism links to the respective development of supplier markets and buyer industry transformation. Originality/value: The focal study provides a holistic approach and conceptualizations with which to balance the perspectives of purchasing as an intra-firm operational function and as a strategic activity embedded in relationship and network management. In particular, the study provides conceptual development on purchasing practices in post-outsourcing relationships and concrete managerial implications for dealing with such circumstances. The focal study includes case notes that facilitate using the study for teaching purposes.